Psychosocial concepts in humanitarian work with children : a review of the concepts and related literature - Loughry, Maryanne; Eyber, Carola (National Academies Press, 2003)
This report is concerned with reviewing psychosocial concepts in research related to humanitarian work, with particular emphasis on research related to children affected by prolonged violence and armed conflict.